Downregulation of the long non-coding RNA FOXD2-AS1 inhibits cell proliferation, migration and invasion in osteosarcoma - Zhang, Haomeng (Mol Med Rep, 2019)
Increasing amounts of long noncoding RNAs (lncRNAs) have been shown to be involved in the development of cancer. Recently, aberrant expression of the lncRNA forkhead box D2 adjacent opposite strand RNA1 (FOXD2-AS1) has been reported to be involved in the progression of several types of human cancer. However, the function and mechanism of FOXD2-AS1 in osteosarcoma (OS) are currently unclear. The present study aimed to investigate the function and mechanism of FOXD2-AS1 in OS. Firstly, it was revealed that the expression levels of FOXD2-AS1 were significantly upregulated in OS tissues and cells, compared with in adjacent tissues and normal cells, as determined using reverse transcription-quantitative polymerase chain reaction. Notably, the overall survival of patients with relatively high FOXD2-AS1 expression in OS tissues was significantly lower than that of patients with relatively low expression, as determined using Kaplan-Meier analysis. In addition, loss-of-function experiments were performed in vivo and in vitro to study the biological effects of FOXD2-AS1. The SOSP-9607 and U2OS OS cell lines were infected with lentivirus-mediated FOXD2-AS1 short hairpin RNA; subsequently, the alterations in cell phenotype and downstream molecules were evaluated. Knockdown of FOXD2-AS1 inhibited the proliferation, migration and invasion of OS cells. Furthermore, the number of cells in the S phase was significantly decreased, which was consistent with the results of the Cell Counting kit 8 proliferation assay. The expression levels of ribonucleotide reductase regulatory subunit M2 and phosphoglycerate dehydrogenase were decreased, as determined by western blotting, following FOXD2-AS1 knockdown. Finally, in a nude mouse model of tumorigenesis, it was revealed that, when FOXD2-AS1 expression was downregulated, tumor growth was significantly reduced and pulmonary metastatic nodules were markedly reduced. The results of the present study suggested that decreased FOXD2-AS1 expression may inhibit the growth, migration and invasion of tumor cells, and it may regulate downstream gene expression. In conclusion, these findings indicated that FOXD2-AS1 may be used as a potential therapeutic target and early tumor marker for the diagnosis and prognosis of OS.